Inter-laboratory comparative testing of petroleum products in test laboratories of russian defense ministry - K. V. Shatalov; I. I. Sorokovova (Тонкие химические технологии, 2014)
The paper contains the procedure of performing and the algorithm of processing the results of comparative tests conducted in petroleum laboratories of the Russian Defense Ministry. Presented herewith is an example of calculations made during attestation of samples for the purpose of control and evaluation of quality of test results obtained in the course of inter-laboratory comparative tests.